Modulation of Lactam‐Lactim Tautomerism of Quinoxalin‐2‐one Induced by Cucurbit[7]uril: A Comparative Study with Oxazin‐2‐one. Issue 39 (22nd October 2018) - Aliaga, Margarita E.; De la Fuente, Julio R.; García‐Rio, Luis; Rojas‐Romo, Carlos; Uribe, Iván; Díaz‐Hernández, Dafne; Fierro, Angélica; Cañete., Álvaro
Abstract: The formation of inclusion complexes between cucurbit[7]uril (CB7) and N, N ‐(dimethylamino)styrylquinoxalin‐2‐one (Me2 NSQx ) or the N, N ‐(dimethylamino)styryloxazin‐2‐one (Me2 NSOxa ) dyes, was carried out using spectroscopy techniques (UV‐vis, fluorescence and NMR), flash photolysis, mass spectrometry and docking studies. Results show that: ( i ) both dyes form inclusion complexes with a CB7 excess, which depicts huge bathochromic shifts (>100 nm); ( ii )Me2 NSQx andMe2 NSOxa, firstly form a 1:1 complex and at higher CB7 concentrations, a 2:1 host:guest complex is generated; ( iii ) the inclusion complex forMe2 NSQx changes from its stable lactam form to the lactim tautomer, while forMe2 NSOxa the equilibrium is shifted to the oxazinium tautomer. Finally, in the case ofMe2 NSQx dye, spectroscopic and docking studies indicate that the most stable complex isMe2 NSQx @CB7 (1:2) in its lactim form, while inMe2 NSOxa the equilibrium is shifted to the oxazinium containing complex. Therefore, our results evidence the importance of the interaction of CB7 as another form of controlling the tautomerism equilibrium of lactam or lactones derivatives. Abstract : The quinoxalin‐2‐one and oxazin‐2‐one derivatives can be structurally modified by an external stimulus, like the interaction with the macrocycle CB7. In particular, in the first case, the encapsulation of 7‐ N, N ‐dimethylamino phenyl group of the lactam form by CB7 lead to that the equilibrium is shifted to its lactim‐containing complex. This form is maintained even when the tautomer of quinoxalinone also is included in CB7, forming a 2:1 host:guest complex. As a consequence, the dye absorption band undergoes a huge shift (>100 nm).